Nothing with strings eaudiobook Npr's beloved holiday stories. - White, Bailey (Tantor Media, 2008)
For more than a decade, Bailey White has delivered a story each Thanksgiving to National Public Radio's All Things Considered listeners. Long awaited by her many fans, Nothing with Strings is the entire collection of these Thanksgiving stories, published together for the first time. With wit and charm, White writes about an almost-gone little town where a spoon player is a guardian angel, an old woman fears that John James Audubon is living in her attic, and a homely governess wins a baby bull in a raffle and loses her heart. It's the kind of place where Heavenly Blue morning glories grow in through the windows of old houses and funeral food is shared on a Greyhound bus on a fall afternoon. You may not have ever been there, but you will feel right at home. White's beautifully written stories, teetering on the edge of the unreal, are sure to bring back memories you don't really have. These are the stories that can be found in Nothing with Strings : "Meals-On-Wheels" "The Long Black Veil" "What Would They Say in Birmingham?" "The Progress of Deglutition" "The Telephone Man" "Miss Wigglesworth's Bull" "Bus Ride" "Return to Sender" "Lonesome Without You" "The Garden" "Nothing with Strings" "The Green Bus" "Almost Gone"